Somatotype, level of competition, and performance in attack in elite male volleyball - Giannopoulos, N.; Vagenas, G.; Noutsos, K.; Barzouka, K.; Bergeles, N. (Journal of Human Kinetics, 2017)
This study investigated the relationship between somatotype, level of competition, and performance in attack in elite level male volleyball players. The objective was to test for the potential covariation of competition level (Division A1 vs. A2) and playing position (hitters vs. centers vs. opposites) considering performance in attack. Anthropometric, body composition and somatotype variables were measured according to the Heath-Carter method. The attack actions of 144 players from 48 volleyball matches were analyzed and their performance was rated using a 5-point numerical scale. Results showed that players of Division A1 were taller, heavier, more muscular, and less endomorphic compared to those of Division A2. MANOVA and follow-up discriminant function analysis revealed somatotype differences among playing positions with centers and opposites being endomorph-ectomorph and hitters being central. Centers performed constantly better than hitters and opposites regardless of the division and somatotype. Multiple linear regression analysis showed that variables defining ectomorph and endomorph players, centers, and players of Division A1 significantly determined the relative performance superiority and were able to explain the variation in performance by almost 25%. These results could be taken into account by coaches when assigning players to particular playing positions or when designing individualized position-specific training programs.